Effectiveness of boria welding flux in improving the wettability of ZrB2 in contact with molten Cu. Issue 12 (September 2018) - Saunders, Theo; Tatarko, Peter; Grasso, Salvatore; Reece, Michael J.
Abstract: In this work boria based welding flux was used to remove the native oxide layer on ZrB2 and promote bonding/wetting with copper. Without boria welding flux the Cu/ZrB2 system showed no wetting. When flux was used at the interface no dissolution or reaction was observed between Cu, ZrB2 and the flux. The effectiveness of boria in dissolving zirconia oxide surface layer was further confirmed on wetting tests carried out on pre-oxidised ZrB2 samples having an oxide scale of 15 μm thickness. A mock joint was made using copper with flux, and it had no trapped porosity induced by the presence of the boria flux. This work suggests a novel, low cost and scalable route to promote joining/wetting of dissimilar materials having melting points differing by 2000 °C.